Sistem Informasi Kepegawaian pada PT Sophia Bara Energi - Jibril Giovanno Andros; Fransiska Prihatini (Fakultas Ilmu Komputer Universitas Sumatera Selatan, 2025)
PT Sophia Bara EnergiIt is a company engaged in the mining sector, specifically coal mining. Established in 2022 in Palembang, the company is headquartered at Jl. Angkatan 45 No. 1088A, Lorok Pakjo, Ilir Barat I District, Palembang City, South Sumatra. Currently, the company still employs conventional methods for employee data management, such as physical documents, manual recording, and paper forms.These Methods result in inefficiencies in recruitment, attendance, leave management, and the handling of promotions and rewards. The research methodology applied in developing the employee information system utilizes the RUP(Rational Unified Process) methodology. The final result of this research is a web-based employee information system application designed to facilitate and streamline the company’s processes